Ultrastructural Plasticity of Cyanobacteria - Baulina, Olga I.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book offers an in-depth analysis of the cell biology of cyanobacteria, a group of phototrophic microorganisms performing an important function in the biosphere. The chapters present the author$1 (Bs and her colleagues$1 (Bpioneering investigations of the ultrastructure of cyanobacteria under high-light and dark conditions, during irradiation by extremely high fluxes of light, in the course of L-transformation and within model associations and natural symbioses with plants. Diverse patterns of ultrastructural change are illustrated in electron micrographs and schematics. The book further introduces a new concept of (3z(Bbacterial ultrastructural plasticity(3y (B- the reversible rearrangement of ultrastructure in response to environmental changes, as a strategy for finding and investigating cell adaptation mechanisms and intraspecies structural diversity of cyanobacteria and other prokaryotes. It serves as a valuable guide for teaching and research in the field of cell biology of microorganisms and plant-cyanobacteria symbioses.s
Introduction -- Ultrastructural Plasticity of Cyanobacteria under Dark and Light Intensity Conditions -- Ultrastructural Plasticity of Cyanobacteria During Enzymatic Induction of L-Transformation -- Ultrastructural Plasticity of Cyanobacteria in Model Associaations with Plant Partners -- Ultrastructural Plasticity of Cyanobacteria in Natural Symbioses with Plants. Conclusion.
Keywords: Life sciences; Cytology; Microbiology; Plant physiology; Life Sciences; Microbiology; Plant Physiology; Cell Biology